2022
DOI: 10.1155/2022/4959487
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of Probiotics and their Derivatives against Biofilm-Producing MRSA: A Scoping Review

Abstract: Background. Methicillin-resistant Staphylococcus aureus (MRSA) is one of the main bacterial pathogens causing chronic infections, mainly because of its capacity to produce biofilm. Biofilm production is one of the underlying strategies for antibacterial drug resistance. Accordingly, preventing and attenuating biofilm production has become an emerging approach to controlling persistent infections. Therefore, this scoping review is aimed at surveying the published literature describing the usage of probiotics an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…Visualizing the biofilm matrix using scanning electron microscopy (SEM) confirmed that treatment with CFS BRD3A resulted in a substantial 50% reduction and disruption of the biofilm matrix of MRSA. Few studies have also shown that lactic acid bacteria such as Lactobacillus species exhibit significant antibacterial and antibiofilm activity against MRSA (Jalalifar et al, 2022 ). Therefore, it can be concluded that CFS BRD3A demonstrated antibacterial properties along with biofilm inhibitory capabilities, which make it an effective therapeutic option against S. aureus infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Visualizing the biofilm matrix using scanning electron microscopy (SEM) confirmed that treatment with CFS BRD3A resulted in a substantial 50% reduction and disruption of the biofilm matrix of MRSA. Few studies have also shown that lactic acid bacteria such as Lactobacillus species exhibit significant antibacterial and antibiofilm activity against MRSA (Jalalifar et al, 2022 ). Therefore, it can be concluded that CFS BRD3A demonstrated antibacterial properties along with biofilm inhibitory capabilities, which make it an effective therapeutic option against S. aureus infections.…”
Section: Discussionmentioning
confidence: 99%
“…MRSA is capable of forming a biofilm on biotic and abiotic surfaces, which enhances its antibiotic resistance and contributes to an increased rate of morbidity and mortality worldwide (Silva et al, 2021 ); therefore, effective therapeutic approaches are needed. Most of the previous studies suggested that lactic acid bacteria (LAB) strains can be used to eradicate biofilm-forming MRSA infections (Jalalifar et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, nisin forms pores responsible for cell lysis; thereby, nisin activity extends to both Gram-positive and -negative bacteria, finding applications in food preservation, veterinary, pharmaceutical, and healthcare devices [94]. Recently, the emerging role of nisin and its derivatives against MRSA was reviewed, reporting an increasing number of studies showing how microorganisms that produce nisin act as probiotics against MRSA [95]. In an interesting study in hospitalized humans, it was observed that microbiota-derived lantibiotics similar to nisin could reverse resistance in vancomycin-resistant Enterococcus faecium, a leading cause of hospital infection [96].…”
Section: Chemical Structure and Mode Of Action For Ampsmentioning
confidence: 99%
“…Various studies demonstrated the ability of probiotic microorganisms to enhance resistance to intestinal infections such as those induced by Lacticaseibacillus rhamnosus GG against rotavirus [1][2][3]. Furthermore, diverse mechanisms through which probiotics can exert antagonistic effects on intestinal pathogens have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, diverse mechanisms through which probiotics can exert antagonistic effects on intestinal pathogens have been reported. Among them, competition for host tissue binding sites; competition for nutrients; production of metabolites affecting the phenotype of pathogens by inhibiting, for example, their growth or biofilm formation; and the modulation of intestinal immune responses have been described [1][2][3]. Through these microbe-microbe and microbe-host interactions, probiotics can help to reduce the severity of intestinal infections [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%